The moderating effect of household income on the determinants of parental contribution to children in Malaysia - Abdullah, Nuraini; Sabri, Mohamad Fazli; Ahmad Suhaimi, Siti Shazwani; Magli, Amirah Shazana; Ithnin, Muslimah (Malaysian Consumer and Family Economics Association, 2023)
Parents undertake the heaviest responsibility ever to prepare children for a brighter future. The study identified predictors towards parental contribution included parental characteristics, child upbringing, parental purchasing behaviour and financial strain. The moderating role of household income also was addressed. The study surveyed 2,182 respondents from low-income households with children under six years old and found that parental contributions towards their children’s upbringing were significantly influenced by household income. Parental characteristics were detected as important drivers of parental contribution; child upbringing and parental purchasing behaviour influence parental contribution positively, but the negative effect of financial strain was revealed. On the other hand, the upbringing of the children and parental contribution made by parents are significant in deciding the household income. The study highlights that parental contributions play a crucial role in shaping children’s character and development. Appropriate investments in children are essential to ensure they become decent human beings. Furthermore, the study underlines the practical implications for parents, government, and non-government organizations regarding investment in children. It is suggested that benefits, such as allowances provided by the Department of Social Welfare, should be allocated to needy families so that parents can invest in their children’s future. This study emphasizes the importance of investing in children from low-income households to ensure a brighter future, and government and non-government organizations must support these families.